Assessment of Biosecurity Status of Broiler Farm at Jamalpur District. - Md. Khademul Islam; A. S. M. Mahbub (University of New South Wales, 2022)
Broiler chicken production is an important source of animal protein supply, but the biosecurity conditions of Jamalpur region are not satisfactory. This study was done to gauge farmers' knowledge of and adherence to biosecurity guidelines of a broiler farm. We visited five randomly selected farms in two unions of Jamalpur district. The questionnaires were developed based on "biosecurity guideline for commercial poultry industry in Bangladesh", provided by the department of livestock services of Bangladesh. There were 143 parameters, and each one of them bears 1 point. For each parameter that a farm followed, it gained one (1) point. The parameters were divided into 5 different principles: isolation, good farm hygiene, flock health care and monitoring, good farm management practices, and compliance with government regulations. Farm hygiene and compliance with government regulations were most commonly ignored principle by all the farms, especially in case of farm worker's hygiene All the farm had trees adjacent to the shed. The highest score was 62 (43.37%), gained by Farm 2, and the lowest point was 37 (25.87%) gained by Farm 1. The average score was 50 (34.97) points. This is the first survey work in this region, but there were difficulties in working with a larger number of farms due to the COVID-19 pandemic with frequent lockdowns. This study may help to improve the biosecurity conditions of broiler chicken production in small stockholders of this region.